Determinants of entrepreneurial engagement levels in Europe and the US - A. Roy Thurik; Isabel Grilo (Max Planck Institute of Economics, 2005)
Determinants from different streams of literature and spanning different disciplines are used to explain entrepreneurial decisions. A multinomial logit model and survey data from the old 15 EU member states, Norway, Iceland, Liechtenstein and the US are used to establish the effect of demographic and other variables on various entrepreneurial engagement levels. These engagement levels range from "never thought about starting a business" to "thinking about it", "taking steps for starting up", "having a young business", "having an older business" and "no longer being an entrepreneur". Data of two Entrepreneurship Flash Eurobarometer surveys (2002 and 2003) containing over 20,000 observations are used. Other than demographic variables, the set of explanatory variables used includes the perception by respondents of ad-ministrative complexities, of availability of financial support and of risk tolerance, the respondents' prefer-ence for self-employment and country specific effects. The most striking result is that the perception of lack of financial support has no discriminative effect across the various levels of entrepreneurial engagement.
Keywords: M13; R12; J23; H10; 330; entrepreneurship; determinants; nascent entrepreneurship; multinominal logit; barries to entry; Europe; Unternehmer; Unternehmensgründung; Markteintritt; Schätzung; EU-Staaten; USA